Kesan penggunaan multimedia interaktif terhadap pembelajaran matematik : kajian di sekolah bestari terpilih di Kuching, Sarawak - Lee, Jun Choi (2004)
A recent years there has been a surge of interest in the used of interactive multimedia in educational computer applications. Based on the postulate that learning is a constructive process, the purpose of this study was to determine the effects of interactive multimedia software on students' mathematics achievement scores. The sample of the experimental study consisted of 216 students selected based on their mathematic achievement (high aptitude, moderate aptitude and low aptitude).